Sustainable Development Clauses in the International Law of the Sea - A. N. Vylegzhanin; A. M. Korzhenyak (Московский журнал международного права, 2023)
INTRODUCTION. The international legal content of the concept of sustainable development, so common in international treaties and sometimes expressed in different terms, undoubtedly requires modern clarification, as well as its place in the system of international law.  Firstly, it is interesting to answer the question of how ideas of sustainable development have resulted in their crystallization as a concept of international law. Secondly, using treaty sources of the international law of the sea, where this notion is particularly common, it is meaningful to identify the intentions of States parties to such treaties to consider sustainable development clauses as legal obligations. Thirdly, it is important to determine whether these clauses now constitute a principle of the international law of the sea or whether they retain the status of separate treaty obligations that are not interrelated.  MATERIALS AND METHODS. The article is based on the analysis primarily of the norms of the international law of the sea, in which the term «sustainable development» is applied, with reference to the scientific and legal literature and judicial decisions relevant to the topic.  The research involves methods of legal construction, legal modeling, analysis and synthesis, systematic, structural-functional, formal-logical, formal-legal, historical and chronological methods.  RESEARCH RESULTS. The analysis of international treaties and other international legal instruments applicable to the issue has shown that the long-standing ideas of «sustainable development» are now normatively well-established; that the provisions of international treaties on sustainable development have already developed as an inter-branch (cross-cutting) principle of international law at the intersection, primarily, of the international law of the sea and international environmental law; that States undertake in practice explicit obligations and exercise relevant rights in the framework of upholding this cross-cutting principle.  The authors’ vision of the content of this principle is offered and its various manifestations in the international law of the sea are shown.  DISCUSSION AND CONCLUSIONS. The study critically evaluates the prevailing view in the Western international legal literature that the idea of sustainable development was suggested by the 1987 Report «Our Common Future» (the Brundtland Report). It has been shown that the idea predates this report, and that the initial mechanisms for sustainable development had already been reflected in existing international treaties by 1987. The suggestion is made that the international legal concept of sustainable development has several cumulative components that together define its content. Among these there are elements that are part of this concept primarily because they are means of achieving sustainable development goals, having a much narrower scope if interpreted in isolation. The international legal principle of sustainable development seeks to resolve the tensions primarily between the States’ right to development and their duty to protect the environment, serving as a nexus that ensures that neither the one nor the other is neglected. Its social dimension is undoubtedly significant, although it has been interpreted very differently in the international legal literature.  In the context of contemporary international law, it is expedient to assert an inter-branch (cross-cutting) nature of the sustainable development principle: its legal content extends beyond the scope of specific branches of international law, including international law of the sea, international environmental and economic law. However, most international treaties of a universal and especially regional character that contain some form of sustainable development clauses currently refer to sources of the international law of the sea, which may certainly change in the future.